Programmable CRISPR‐Cas transcriptional activation in bacteria - Hsing‐I Ho; Jennifer R Fang; Jacky Cheung; Harris H Wang (Molecular Systems Biology)
Abstract Programmable gene activation enables fine‐tuned regulation of endogenous and synthetic gene circuits to control cellular behavior. While CRISPR‐Cas‐mediated gene activation has been extensively developed for eukaryotic systems, similar strategies have been difficult to implement in bacteria. Here, we present a generalizable platform for screening and selection of functional bacterial CRISPR‐Cas transcription activators. Using this platform, we identified a novel CRISPR activator, dCas9‐AsiA, that could activate gene expression by more than 200‐fold across genomic and plasmid targets with diverse promoters after directed evolution. The evolved dCas9‐AsiA can simultaneously mediate activation and repression of bacterial regulons in E. coli. We further identified hundreds of promoters with varying basal expression that could be induced by dCas9‐AsiA, which provides a rich resource of genetic parts for inducible gene activation. Finally, we show that dCas9‐AsiA can be ported to other bacteria of clinical and bioindustrial relevance, thus enabling bacterial CRISPRa in more application areas. This work expands the toolbox for programmable gene regulation in bacteria and provides a useful resource for future engineering of other bacterial CRISPR‐based gene regulators.